PERLINDUNGAN HUKUM TERHADAP PENERBIT SEBAGAI PEMEGANG HAK CIPTA TERHADAP TINDAKAN PEMBAJAKAN BUKU - Dimaz Anugrah Antari (LEGAL OPINION, 2024)
The conclusions in this study are: Protection of a copyrighted work, especially books that are rampantly offered on the market, in this case the appreciation of copyrighted works is still low, so that the protection can not be fulfilled optimally, even far from perfect. It can be said that the needs and economic conditions, and the need for books support the circulation of pirated books. This phenomenon seems to be a familiar culture and is interrelated with each other, namely between publishers, traders, and book lovers, namely the community itself. In addition to cultural factors, the weak role of the authorities in conducting raids will be a factor in the existence of pirated books that are rampant in the market. The cause of rampant book piracy, lack of respect for copyright is the reason of a person's personality in viewing the level of respect for copyright. ABSTRAK Adapun kesimpulan dalam penelitian ini adalah: Perlindungan terhadap sebuah karya cipta khususnya buku yang marak ditawarkan di pasaran, dalam hal ini penghargaan akan karya cipta masih rendah, sehingga perlindungannya-pun belum dapat dipenuhi secara optimal, bahkan jauh dari sempurna. Dapat dikatakan bahwa kebutuhan dan keadaan ekonomi, dan kebutuhan akan buku mendukung beredarnya buku bajakan. Fenomena ini seolah menjadi budaya yang sudah biasa dan saling berkaitan satu sama lain yaitu antara penerbit, pedagang, dan penikmat buku yaitu masyarakat sendiri. Selain karena faktor budaya, lemahnya peran aparat dalam melakukan razia akan menjadikan faktor keberadaan buku bajakan yang marak terjadi di pasaran.